A Literature Review Exploring the Effectiveness and Challenges of Charismatic Leadership of Kiai in the Transformation and Preservation of Islamic Educational Values - Rahma; Andi Indriani Ibrahim; Syahbudin Adam; Zazabila; Mutiara; Agita; Pratiwi; Putri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The charismatic leadership of a kiai (Islamic scholar) plays a central role in Islamic education, especially in pesantren (Islamic boarding schools) as traditional educational institutions that still exist today. The charisma of a kiai is not only reflected in their authority but also in their ability to mobilize students, the community, and the educational environment to maintain Islamic values amidst modernization. However, the challenges of globalization, technological advancements, and changing mindsets of the younger generation require kiai leadership to continuously adapt without losing its authenticity. Therefore, it is important to conduct a literature review that explores the effectiveness and challenges of charismatic kiai leadership in transforming and preserving the values of Islamic education. To explore the effectiveness of charismatic kiai leadership and the challenges faced in preserving the values of Islamic education. The study was conducted through a literature review of various research papers, journals, and relevant scholarly works. Charismatic kiai leadership is effective in building loyalty, maintaining pesantren traditions, and adapting learning to contemporary developments. The main challenges include the influence of globalization, popular culture, limited resources, and the demands of technological adaptation. Charismatic kiai leadership has proven capable of maintaining the continuity of Islamic education values, but it needs to be supported by adaptive and innovative strategies to remain relevant in the modern era.".